Strategi Pembelajaran Guru PAI dalam Pembinaan Pola Interaksi Sosial Siswa di SDN 02 Sialang Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Laila Niswah; Puti Andam Dewi (YASIN, 2026)
Although the learning strategies used by Islamic Religious Education teachers to foster students’ patterns of social interaction have received attention in various studies, studies that specifically discuss the implementation of the brainstorming method at the elementary school level remain limited. This study aims to describe the learning strategies used by Islamic Religious Education teachers to foster students’ patterns of social interaction at SD Negeri 02 Sialang, Kapur IX Subdistrict, Lima Puluh Kota Regency. This study used a qualitative approach with a case study design. The research participants consisted of Islamic Religious Education teachers, the principal, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results show that teachers applied cooperative learning strategies through the brainstorming method, supported by the use of learning media and effective classroom management. This strategy was able to increase students’ activeness in discussion, expressing opinions, working collaboratively, and building positive social interactions during the learning process. However, several students were still found to lack self-confidence and had not participated optimally. The conclusion of this study affirms that cooperative learning strategies based on the brainstorming method can support the development of students’ patterns of social interaction in Islamic Religious Education learning. The implications of this study include theoretical contributions to the development of studies on Islamic Religious Education learning strategies and practical implications for teachers in designing learning that is more active, collaborative, and oriented toward shaping students’ social character.